Fatores pré-operatórios associados à injúria renal aguda após cirurgia cardíaca: estudo prospectivo - Kochi, Ana Claudia [UNESP]; Martins, Antonio Sérgio [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Martin, Luis Cuadrado [UNESP]; Balbi, André Luis [UNESP] (Associação Médica Brasileira, 2008)
OBJECTIVES. To evaluate the clinical characteristics and co-morbidities associated with development of Acute kidney injury (AKI) after cardiac surgery in patients of a predominantly tertiary care university hospital.METHODS. One hundred and fifty cardiac surgery patients were prospectively studied at the Botucatu School of Medicine, University Hospital- UNEP, using a protocol which started 48h before and finished 48h after surgery, AKI was defined as a 30% increase in baseline serum creatinine.RESULTS. Were expressed as mean +/- standard deviation or median, with a significance level of 5%. Results: There was a slight male predominance (57%); mean age of the studied population, was 56 +/- 14 years. Sixty-five per cent of patients underwent myocardial revascularization. AKI was diagnosed in 34% of cases, Multivariate analysis showed that age over 60 years and peripheral vascular disease were significant associated with AKI developmentCONCLUSION. AKI was a common complication in cardiac surgery patients at this hospital, AKI was associated with age over 60 years and presence of peripheral vascular disease.
Preoperative factors for the development of acute kidney injury after cardiac surgery: Prospective study
Keywords: acute kidney injury; acute renal failure; cardiac surgery; complications